A Study on Combustion Characteristics of Insensitive Triple-Base Propellant - Yilan Yang; Tianyi Zhu; Zhiyu Yan; Qianqian Li; Bo Liu; Jinhua Wang; Zuohua Huang (Applied Sciences, 2023)
Research on combustion characteristics can provide basic information and theoretical support for the design of insensitive propellant. This work aims to investigate the combustion characteristics of insensitive triple-base propellant. All propellants were prepared based on same triple-base propellant, but they were desensitized with the same desensitizer in different ways. The high-speed camera, spontaneous luminescence, NO, NH chemiluminescence, and OH-planar laser induction fluorescence (PLIF) methods were employed to capture the combustion flame and derive the distributions of important intermediates. Results show that ignition delay times of insensitive propellants are obviously longer. This indicated that the application of the desensitizer has a partly hindering effect on the early ignition stage. The combustion time of insensitive propellants is mostly similar, which means that the desensitizer has little influence on the intensity of actual combustion. The change in flame height and area of insensitive propellants over time indicated that the combustion progressivity of some insensitive propellants was more prominent, which means that the desensitizer concentration and desensitizing methods all affect the performance of insensitive propellant. The signal intensities of NO and NH show a negative correlation, indicating that a competitive relationship probably exists between the formation of NO and NH radicals during the reaction process. The high concentration of OH mainly locates outside NO, suggesting that there may be a transformation between NO and OH. The maximum signal intensity of NO and NH of different insensitive propellants confirmed that both the concentration of desensitizers and the desensitizing methods exhibit important effect on the reaction process.